Reduced cell proliferation in the dentate gyrusis not correlated with the development of learned helplessness - Vollmayr, Barbara; Simonis, Claudia; Weber, Silja; Gass, Peter; Henn, Fritz A. (Biological psychiatry, 2003)
Background - A plethora of indirect findings suggests that mood disorders may be caused by or result in structural changes in the brain, namely decreased hippocampal cell proliferation. - Methods - To test for these hypotheses, we used a rat model of depression, learned helplessness. Moderate unpredictable and inescapable foot shocks induced learned helplessness only in a portion of the rats. Rats that showed helpless behavior were compared to those behaving normally after inescapable shock. Proliferating cells in the dentate gyrus were labeled with BrdU (bromodeoxyuridine). - Results - Helpless behavior appeared before the decrease of dentate gyrus cell proliferation was maximal. Cell proliferation was decreased to the same extent in animals that developed helplessness as those that were not helpless. Furthermore, immobilization stress, which reduced the rate of cell proliferation, did not induce learned helplessness. - Conclusion - These results are in line with reports that the rate of dentate gyrus cell proliferation is acutely down-regulated by stress, but the development of helpless behavior does not correlate with this process. Further studies will have to clarify if during learned helpless behavior neurogenesis is impaired by altered differentiation or survival of cells.